Practicing interdisciplinarity : convergences and contestations - Remesh, Babu P.; Kumar, Ratheesh (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This book examines the epistemological, social and political perspectives of practicing interdisciplinary approaches to enhance knowledge, pedagogy, and methodological research in the South Asian context. The volume sets the context by bringing together a range of ideas, questions and reflections on the concept of interdisciplinarity, the four waves of interdisciplinarity in contemporary history of knowledge, which were radically different from each other in their epistemological and political orientations, and the evolution of organization of knowledge. The book redefines the concept of interdisciplinarity and takes into cognizance the importance of the mutual shaping of politics and knowledge in our search for inclusive and sustainable future(s). The book offers a blend of both conceptual and academic discourses on interdisciplinarity and the personal experiences of leading practitioners, bringing together critical engagements from different vantage points on practicing it. It will be of interest to researchers, scholars and practitioners of social sciences and humanities disciplines as well as interdisciplinary fields such as educational studies, development studies, women's studies, media studies, cultural studies, urban studies, labour studies, legal studies, public health, disability studies, global/international studies and performing arts. It will also be useful for policy planners, development practitioners, activists and social organizers working in related fields"--
Keywords: Social sciences -- Research -- South Asia; Interdisciplinary approach to knowledge; Interdisciplinary research -- South Asia; SOCIAL SCIENCE / General; EDUCATION / General